Deciphering the sequential changes of monocytes/macrophages in the progression of IDD with longitudinal approach using single-cell transcriptome - Li, Weihang; Zhao, Yingjing; Wang, Yongchun; He, Zhijian; Zhang, Linyuan; Yuan, Bin; Li, Chengfei; Luo, Zhuojing; Gao, Bo; Yan, Ming (Frontiers in Immunology, 2023)
Intervertebral disk degeneration (IDD) is a chronic inflammatory disease with intricate connections between immune infiltration and oxidative stress (OS). Complex cell niches exist in degenerative intervertebral disk (IVD) and interact with each other and regulate the disk homeostasis together. However, few studies have used longitudinal approach to describe the immune response of IDD progression. Here, we conducted conjoint analysis of bulk-RNA sequencing and single-cell sequencing, together with a series of techniques like weighted gene co-expression network analysis (WGCNA), immune infiltration analysis, and differential analysis, to systematically decipher the difference in OS-related functions of different cell populations within degenerative IVD tissues, and further depicted the longitudinal alterations of immune cells, especially monocytes/macrophages in the progression of IDD. The OS-related genes CYP1A1, MMP1, CCND1, and NQO1 are highly expressed and might be diagnostic biomarkers for the progression of IDD. Further landscape of IVD microenvironment showed distinct changes in cell proportions and characteristics at late degeneration compared to early degeneration of IDD. Monocytes/macrophages were classified into five distinct subpopulations with different roles. The trajectory lineage analysis revealed transcriptome alterations from effector monocytes/macrophages and regulatory macrophages to other subtypes during the evolution process and identified monocytes/macrophage subpopulations that had rapidly experienced the activation of inflammatory or anti-inflammatory responses. This study further proposed that personalized therapeutic strategies are needed to be formulated based on specific monocyte/macrophage subtypes and degenerative stages of IDD.